(untitled) (Applied Biological Research, 2018)
Among the various laboratory animals, mice and rats with their extensive use in bioscience research, have achieved an unparalleled level. These animals are no different from others with respect to the possibilities of adventitious and opportunistic infections. These organisms usually do not cause any clinical disease but instead causes physiological alterations rendering the animals unsuitable for experimental studies. Although the number and prevalence of these pathogens have declined considerably, but many are still around and may infect the colony. Facial abscess is the one among such infections and the present report describes the microbiology and histopathology of a mandibulofacial abscess. Earlier, a few cases of natural occurrence of maxillofacial abscesses in mice has been reported (Lawson, 2010); however, the present case is first of its kind with dual infection of methicillin resistant Staphylococcus aureus (MRSA) and Pseudomonas aeruginosa resistant against multiple antimicrobial drugs.